Isolated bidirectional full-bridge dcadc converter with fly back snubber for high-power applications (Global Journals of Research in Engineering, 2012)
This paper introduces a flyback snubber to recycle the absorbed energy in the clamping capacitor. The flyback snubber can be operated independently to regulate the voltage of the clamping capacitor; therefore, it can clamp the voltage to a desired level just slightly higher than the voltage across the low-side transformer winding. Since the current does not circulate through the full-bridge switches, their current stresses can be reduced dramatically under heavyload condition, thus improving system reliability significantly.
Keywords: flyback snubber; clamping capacitor; transformer winding; full-bridge switches; system reliability